2017
DOI: 10.4236/ojrad.2017.74028
|View full text |Cite
|
Sign up to set email alerts
|

Echo-Mammographic and Anatomo-Pathological Aspects of Male Breast Cancer in Togo

Abstract: Studies of male breast cancer are rare in Africa. In Togo in particular, no work has focused on the epidemiological, mammo-echographic, pathological, therapeutic or prognostic aspects of male breast cancer. The aim of this study is to report cases of male breast cancer in Togo by describing the main epidemiological, mammo-echographic and pathological aspects. This was a retrospective, descriptive and analytical study of 10 cases of male patients presenting with breast cancer confirmed by the pathologic examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Malignant tumors were exclusively represented by infiltrating ductal carcinomas according to several authors [6] [15]. The average age of onset was similar to other authors [16] [17] [18].…”
Section: Histopathological Aspects Of Nodulessupporting
confidence: 80%
See 3 more Smart Citations
“…Malignant tumors were exclusively represented by infiltrating ductal carcinomas according to several authors [6] [15]. The average age of onset was similar to other authors [16] [17] [18].…”
Section: Histopathological Aspects Of Nodulessupporting
confidence: 80%
“…Western authors found an average age of 63 -69 years [11] [12]. In sub-Saharan Africa, N'Timon et al [6] reported found an average age of 55 and Kidmas et al [5] in Nigeria, an average age of 57.9 years.…”
Section: Mammo-echographic Aspectsmentioning
confidence: 95%
See 2 more Smart Citations
“…Some studies have even found that ultrasound and clinical examination may be enough to decide what to do with a breast lesion in the male subject [ 18 ]. In Africa, there are a few studies on the radiopathological correlation of lesions suspected of breast cancer in men, such as that of N'timon et al [ 19 ] in Togo and Ouedraogo et al [ 20 ] in Burkina Faso. N'timon et al in their study only considered the correlation of ACR4 and 5 lesions in imaging and the histological results of ultrasound-guided microbiopsies.…”
Section: Discussionmentioning
confidence: 99%